Perfil psicológico de hombres agresores sexuales de menores de edad, recluidos en centros penitenciarios (2021)
The purpose of this research is to analyse the psychological profile of three (3) male sexual aggressors of minors held in the penitentiary centre of the city of Palmira (V). The legal provisions on sexual offences in Colombia, research precedents and theoretical approaches that explain the behaviour of sexual offenders were taken into account. The methodology used is qualitative, obtaining information through the application of the Minnesota Multiphasic Inventory Abbreviated Version, Tree tests and a general interview, showing antisocial personality traits, poor impulse control and family structures with diffuse or absent father figures.